2022
DOI: 10.1126/sciadv.abq2945
|View full text |Cite
|
Sign up to set email alerts
|

RNA binding protein RBM46 regulates mitotic-to-meiotic transition in spermatogenesis

Abstract: Meiosis entry during spermatogenesis requires reprogramming from mitotic to meiotic gene expression profiles. Transcriptional regulation has been extensively studied in meiosis entry, but gain of function for master transcription factors is insufficient to down-regulate mitotic genes. RNA helicase YTHDC2 and its partner MEIOC emerge as essential posttranscriptional regulators of meiotic entry. However, it is unclear what governs the RNA binding specificity of YTHDC2/MEIOC. Here, we identified RNA binding prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 59 publications
3
25
0
Order By: Relevance
“…YTHDC2 may associate with specific protein complexes at different cell stages, leading to diverse, stage-specific molecular outcomes on RNA targets. Similar RBM46 IP Mass-spec experiments performed in P12 and P21 mouse testes revealed a number of RBM46-associated proteins, several of which were also present in the YTHDC2 protein complexes we identified, including MEIOC, PABPC1, MOV10 and UPF1 (Qian et al, 2022).…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…YTHDC2 may associate with specific protein complexes at different cell stages, leading to diverse, stage-specific molecular outcomes on RNA targets. Similar RBM46 IP Mass-spec experiments performed in P12 and P21 mouse testes revealed a number of RBM46-associated proteins, several of which were also present in the YTHDC2 protein complexes we identified, including MEIOC, PABPC1, MOV10 and UPF1 (Qian et al, 2022).…”
Section: Discussionsupporting
confidence: 73%
“…Our previous studies revealed that in Ythdc2 null mutant mice, a large number of germ cells underwent abnormal chromosome condensation soon after initiating meiotic prophase (Bailey et al, 2017), visible as abnormal metaphase-like spermatocytes in P12 testes. This phenotype was also observed in Meioc and Rbm46 knockout males (Abby et al, 2016;Qian et al, 2022;Soh et al, 2017). Quantification of testis tubule cross-sections revealed that only a small percentage of tubules in Ythdc2 cKO mice contained cells with condensed chromosomes.…”
Section: Ythdc2 Is Required For Late Spermatocytes To Progress Throug...mentioning
confidence: 59%
See 3 more Smart Citations